Pemanfaatan Sistem Informasi Geografis Berbasis Web untuk Penyebaran Lokasi Puskesmas di Kota Tangerang - Ruli Supriati; Sugeng Santoso; Anjar Juniarno (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2014)
Community Health Center or in short is needed for the Indonesian people in general,especially when the present is the cost of treatment is very expensive for most people that'snecessary Indonesia. For dable choice health facilities such as health centers. It required aweb-based geographic information system that provides information about the location ofhealth centers in the city of Tangerang. Geographic information systems (GIS) in the searchlocation would require a layout or a position known as geographic information. Geographicalinformation of the most widely used public at this time that the Google Maps application. In thedesign and development of applications, used waterfall model and source data used in thisstudy, namely Tangerang City Map obtained from Google Maps API and the health cliniclocation data that was obtained from the health department and health center TangerangTangerang City. The result is that there is a system application that can be operated by thepublic in order to determine the location of the health center in the city of Tangerang. So thatpeople can know the location of health centers simply by using a key word to search thelocation of health centers. Geographical Information Systems can figure out the path to bepassed to the health clinic.